2009
DOI: 10.5951/jresematheduc.40.4.0363
|View full text |Cite
|
Sign up to set email alerts
|

Reconceiving Fidelity of Implementation: An Investigation of Elementary

Abstract: Recent research on mathematics reforms in the United States indicates that the reforms are not yet widely implemented. Generally, this claim results from looking at the extent to which teachers use curricular materials or engage in particular classroom practices. This article moves beyond disparate questions of use and practice to examine interactions between teachers and curricula as evidenced by their enactments of whole-number lessons from a Standards-based curriculum. Specifically, we analyze videorecorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…The data show that teachers play an important role in how instructional materials are enacted, and while the instructional materials can exert a considerable influence on the kinds of activity enacted in classrooms, instructional materials alone do not determine the enacted activity and discourse, as evidenced in our participants and in prior research (Brown et al, 2009;Tarr et al, 2008). The variation in both DM and TD groups speaks to the role of the teachers and to factors related to the local instructional context, as noted above.…”
Section: Other Factors That May Account For Trendssupporting
confidence: 44%
See 1 more Smart Citation
“…The data show that teachers play an important role in how instructional materials are enacted, and while the instructional materials can exert a considerable influence on the kinds of activity enacted in classrooms, instructional materials alone do not determine the enacted activity and discourse, as evidenced in our participants and in prior research (Brown et al, 2009;Tarr et al, 2008). The variation in both DM and TD groups speaks to the role of the teachers and to factors related to the local instructional context, as noted above.…”
Section: Other Factors That May Account For Trendssupporting
confidence: 44%
“…Previous research that examined the interaction between curriculum type and instructional practices has shown that, when teachers are newly introduced to high demand tasks, they often reduce the complexity and demand of tasks (Stein et al, 1996). Other research has shown that instructional practices and enactments often do not align with the designers' intentions (Brown et al, 2009;Tarr et al, 2008). In the U.S., this lack of alignment is especially prevalent for instructional materials based on the standards documents from the National Council of Teachers of Mathematics [NCTM] (National Council of Teachers of Mathematics, 1989Mathematics, , 2000.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, in attempts to target lesson objectives and standards, as well as implement a new mathematical curriculum, research suggests that practicing teachers have difficulties in enacting and integrating lessons and the curriculum as intended (Brown et al, 2009; Moloi et al, 2008; Zacharos et al, 2014), which may be mediated by an over-reliance on textbooks (Henry and Brown, 2008), inadequate resources (Hu et al, 2014), or a lack of evidence-based strategies (Phillips and Morse, 2011). On the other hand, in a study conducted by Stein and Kaufman (2010), the findings indicated that practicing teachers’ implementation of the Investigations (textbook series) afforded them opportunities to maintain high cognitive demand, attend to students’ thinking and reasoning, and plan lessons with big mathematical ideas in mind when compared to practicing teachers’ implementation of the Everyday Mathematics (textbook series).…”
Section: Resultsmentioning
confidence: 99%
“…Howson and Wilson (1986) described differences in curriculum implementation by the terms intended curriculum (that which is prescribed by policymakers), implemented curriculum (the one that is enacted by teachers), and attained curriculum (the one that is learned by students). Research has shown frequent inconsistency in the fidelity of curriculum implementation, resulting in incongruity between the intended, the implemented, and the attained curriculum (O’Donnell, 2008; Brown et al , 2009). This study focuses on the teachers’ use of the intended curriculum, that is; ‘the overt curriculum that is acknowledged in policy statements as that which schools or other educational institutions or arrangements set out to accomplish’ (Schubert, 2010, p. 489).…”
Section: Teachers and Curriculum Reformmentioning
confidence: 99%